Specific Binding Sites for Triiodothyronine in the Plasma Membrane of Rat Thymocytes: CORRELATION WITH BIOCHEMICAL RESPONSES - Segal, Joseph (1982)
As a prerequisite to studies of whether the plasma membrane of the rat thymocyte contains specific, saturable binding sites for the thyroid hormone 3,5,3′-triiodothyronine (T(3)), a method was developed for the isolation of a plasma membrane fraction from these cells. As judged from both electron microscopic and marker enzyme studies, the fraction was composed principally of plasma membrane vesicles, was free of nuclear contaminants, and was only slightly contaminated with other subcellular components. At 37°C and pH 7.4, binding of [(125)I]T(3) by the fresh membrane preparation was rapid, reaching a maximum at 5 min and then declining with time, so that by 60 min binding was virtually nil. Decreased binding with time was due to a loss of functional binding sites, but did not reflect desensitization, since the decrease in binding activity with time was independent of the presence or absence of T(3). Scatchard analysis of saturation studies revealed the presence of two binding sites, one with an apparent dissociation constant (K(d)) of 0.95 nM and a maximum capacity of 5.3 × 10(10) sites/100 μg protein, and the other with an apparent K(d) of 25 nM and a binding capacity of 1.4 × 10(12) sites/100 μg protein. Measurement of the ability of several thyronine analogues to inhibit the binding of [(125)I]T(3) revealed the following rank order of potency: l-T(3) > l-T(4) > d-T(3) = d-T(4) > l-3,5-T(2) > rT(3) > d,l-thyronine. Binding of T(3) was inhibited by the omission of calcium from the medium or by the addition of the beta adrenergic antagonist alprenolol. As judged from studies of the lower affinity binding site, these manipulations decreased the affinity, but not the number, of binding sites for T(3). The relative potencies of thyronine analogues to inhibit the binding of [(125)I]T(3) were generally parallel to their previously reported potencies in stimulating the uptake of the sugar analogue 2-deoxy-glucose (2-DG) in intact rat thymocytes in vitro. Further, the inhibition of T(3)-binding produced by l-alprenolol or by excluding calcium from the medium resembled the previously reported inhibition that these manipulations produce with respect to T(3)-induced enhancement of 2-DG uptake. These findings suggest that the binding sites for T(3) present in the plasma membrane of rat thymocytes act as functional receptors linked to the stimulation of 2-DG uptake that T(3) induces in these cells.